Knowledge and Attitudes towards Premarital Screening among Adolescents: A study in a University Setting - Annisa Triska Almanda Dewi; Ari Indra Susanti; Fedri Ruluwedrata Rinawan; Sharon Gondodiputro; Neneng Martini (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Premarital screening (PMS) is an action to prevent the occurrence of genetic and the transmission of infectious diseases. The screening has been recommended and promoted in Indonesia. This study aimed to assess the level of knowledge and attitudes towards premarital screening among teenagers in a university setting.Methods: This study used a cross-sectional design, including 310 adolescents aged 18–21 years at obtained through a non-random consecutive sampling at Universitas Padjadjaran. The data was collected from October 2020 until January 2021 using a close-ended questionnaire, assessing knowledge and attitude towards the PMS. The frequency knowledge level was grouped as good, moderate, and poor. The attitude level was categorized as positive and negative.Results: Most of the respondents (90.3%) had good knowledge of PMS. Respondents who had positive attitudes (79%) strong agreed that carrying out PMS was important, and 51% perceived that PMS needed to be a mandatory procedure before marriage. However, 59.6% had no idea how to deal if the result of the PMS was positive.Conclusion: In general, adolescents at Universitas Padjadjaran have good knowledge and a positive attitude towards PMS. However, comprehensive information about PMS is still needed, especially on decision points that must be taken after getting the test results.